Identification of national research priorities in COVID-19 (SARS-CoV-2) and other respiratory viruses with pandemic potential: Description of the Peruvian experience - Roque-Henriquez, Joel Christian (2023)
Research priorities are a fundamental component of national health research systems. In the year 2021, the National Institute of Health led the process of identifying the "national research priorities in COVID-19 (SARS-CoV-2) and other respiratory viruses with pandemic potential: Preparing for the next pandemic, 2022-2026”. The process was developed following the previous methodology for identification of research priorities used by the Instituto Nacional de Salud (Perú), which was to be adapted to a virtual environment, with four phases. Six strategic objectives to be achieved were formulated and served as an umbrella for the identification of national priorities, a total of 21 research priorities were identified. It is recommended that a plan for the implementation of research priorities be formulated and executed and that the Ministry of Health, through its different instances, take the necessary steps to obtain and allocate resources to the generation of evidence within the framework of priorities.